The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2478/dim-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Which Message? Which Channel? Which Customer? - Exploring Response Rates in Multi-Channel Marketing Using Short-Form Advertising

Abstract: Formulating short-form advertising messages with little ad content that work and choosing high-performing channels to disseminate them are persistent challenges in multichannel marketing. Drawing on the persuasive systems design (PSD) model, we experimented with 33,848 actual customers of an international telecom company. In a real-life setting, we compared the effectiveness of three persuasion strategies (rational, emotional, and social) tested in three marketing channels (short message service (SMS), social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
(98 reference statements)
1
1
0
Order By: Relevance
“…The findings of the study suggested that character presence and cultural aspect are significantly related to each other. This finding is consistent with those of Marzouk et al (2021), who claim that character presence is crucial for effective advertising using advergames in order to have a favourable impact on the brand outcomes while taking the cultural factor into consideration. Also, this finding is similar to the results of Masuda and Nisbett (2001) as they state that culture impacts the perceptual processes like East Asians and North Americans have different percieving and thinking style.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the study suggested that character presence and cultural aspect are significantly related to each other. This finding is consistent with those of Marzouk et al (2021), who claim that character presence is crucial for effective advertising using advergames in order to have a favourable impact on the brand outcomes while taking the cultural factor into consideration. Also, this finding is similar to the results of Masuda and Nisbett (2001) as they state that culture impacts the perceptual processes like East Asians and North Americans have different percieving and thinking style.…”
Section: Discussionsupporting
confidence: 91%
“…Several researches have looked into how well characters work in emotive advertising. Marzouk et al (2021) but not many have explored the influence of character presence on brand outcomes in advergames from cross-cultural aspect. By conducting an empirical study to determine the character presence in advertising video games and its impact on brand outcome from a cross-cultural point of view, this study solves the aforementioned gap.…”
Section: Introductionmentioning
confidence: 99%